The Effect of Plyometric Depth Jump on Students' Jumping Smash Ability in Badminton - Ryan Ma'ruf Efendi; Topo Yono; Ahmad Sulaiman (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2025)
This study aims to determine whether there is an effect of plyometric depth jump on the ability to do jumping smash in badminton games in MTs Darul Kholili students. This study uses the static-group-pretest-posttest design, with a sample of MTs Darul Kholili students from the entire population of 86 people and a sample of 32 people with a random sampling technique. Jump height data is measured using a vertical jump with meters as the unit. Data analysis uses the t test. The results showed that there was a significant difference in the height of the smash jump between the experimental group and the control group (t count = 4.935> t table 2.042). So it can be concluded that plyometric depth jump training has an effect on the height of the jumping smash jump in badminton games.